Namibia : Selected Issues. (IMF Staff Country Reports; Country Report, 2014)
This Selected Issues paper analyzes policies that can raise potential growth in small middle-income countries (SMICs) of sub-Saharan Africa (SSA). The findings suggest that although macroeconomic stability and trade openness are necessary for productivity growth, they are not sufficient. SMICs in SSA need to improve the quality of their public spending, most notably on education, to solve the problem of skill mismatch in the labor market, reduce the regulatory burden on firms, improve access to financing by small and medium-size enterprises, and pave the way for structural transformation in these economies. Given the short-term cost of these reforms, the timing and sequencing of reforms and the role of quick wins is important for their implementation. In some cases, a social bargain can be a mechanism to generate consensus around a package of mutually reinforcing reforms.